2010
DOI: 10.1002/cm.20460
|View full text |Cite
|
Sign up to set email alerts
|

The mechanical properties of a cell, as determined by its actin cytoskeleton, are important for nanoneedle insertion into a living cell

Abstract: Previously, we reported that a nanoneedle of 200 nm diameter manipulated by an atomic force microscope apparatus could be inserted into a living cell. The insertion probabilities varied according to cell type. However, the nanoneedle was never successfully inserted into artificial liposomes. In the current study, we found that the stress fibers and actin filaments comprising the plasmalemmal undercoat are important, determining factors as to whether a nanoneedle can be successfully inserted into a cell. Depoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 33 publications
3
52
1
Order By: Relevance
“…AFM has been used to study the penetration of synthetic lipid bilayers (26)(27)(28)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) and live cells (9)(10)(11)(12)24,29,46,47) by nanoprobes, but the reported membrane penetration forces range from <1 nN to >20 nN (12,29), and the variety of probe types, lipids, and other experimental variables make comparisons across studies difficult.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…AFM has been used to study the penetration of synthetic lipid bilayers (26)(27)(28)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) and live cells (9)(10)(11)(12)24,29,46,47) by nanoprobes, but the reported membrane penetration forces range from <1 nN to >20 nN (12,29), and the variety of probe types, lipids, and other experimental variables make comparisons across studies difficult.…”
Section: Introductionmentioning
confidence: 98%
“…To separate lipid bilayer penetration from other force-relaxation events, we used the breakthrough signatures in synthetic lipid stacks as a template for detecting penetration events in cells. Because synthetic and cellular bilayers differ considerably in their structure and composition, we also chose an intermediate system for comparison: cells whose cytoskeleton was chemically disrupted by cytochalasin D (10). Such cells have intact cell surfaces and native membrane composition, but no underlying cortical cytoskeleton to provide rigidity to the plasma membrane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…52 Actin cytoskeleton determines the mechanical properties of a cell. 53 When macrophage phagocytosis was activated, a rapid accumulation of F-actin and associated proteins in the periphagosomal region occurred. 8 This phenomenon can be clearly seen in Figure 7A,B.…”
Section: Resultsmentioning
confidence: 99%
“…This also is in reasonable agreement with our results, especially taking into account that incorporating peptides into lipid bilayers (hence getting a model somewhat closer to a cell membrane) makes them easier to break, according to micropipette aspiration (44) and AFM indentation (42) measurements. Kagiwada et al (45) reported that a typical force of 3 nN is required to insert a nanoneedle of 200 nm in diameter into a cell. Here, the contact area is critical when estimating a compressive force: although using Eq.…”
Section: Discussionmentioning
confidence: 99%